A review of technical and quality assessment considerations of audio-visual and web-conferencing focus groups in qualitative health research - Hiba Bawadi (3436379) (2023)
The transition from the conventional approach to an online setting in conducting focus groups (FGs) for qualitative research is an increasingly adopted approach in health-related research. The purpose of this narrative review aims to provide an overview of the quality of FGs in health-related research that are conducted using various audio–visual (AV)-enabled and web-conferencing approaches. Online databases searched were Medline/PubMed, ProQuest, Web of Science, and Google Scholar. Four key concepts (qualitative health-related research, online platforms, platform analysis, and quality measures) were used. A consensus group method, and a review of user guides of three of the currently used online platforms (i.e., “WebEx”, “Zoom”, and “Microsoft Teams”) were employed to develop a set of specific core quality criteria for appraising online qualitative research studies. While various synchronous and asynchronous online FG approaches were utilized in health-related research, audio–visual (AV)-enabled, and web-conferencing approaches were comparable to conventional FGs. These platforms are associated with several advantages, such as spontaneity in responses through real-time interactions among researchers and participants. The developed quality assessment tool for online FGs included criteria such as maintaining the privacy of participants and confidentiality of data collected, appraising the potential selection bias due to technological and logistical requirements, and ensuring the presence of features for recording video and audio within the software. The validated quality criteria that are used to evaluate face-to-face qualitative studies can be applicable in online contexts. However, additional criteria targeting the new features of the online platforms should be considered as well. This review helps health-related researchers and research academic institutions to select the online platform that best addresses their research and institutional needs while maintaining good quality, time-efficient, and cost-effectiveness. Other Information Published in: Humanities and Social Sciences Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41599-023-01989-0